2021
DOI: 10.1021/acs.jpcc.1c05599
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-like Thermal Relaxation of Nanoscale Explosive Hot Spots

Abstract: Hot spots are local regions of high temperature that are widely considered to govern explosive initiation. Hot spot dynamics rests on a delicate balance between heat generation due to chemical reactions and heat loss through thermal conduction, making accurate determinations of the conductivity under extreme conditions a key component of predictive explosive models. We develop here an approach to directly determine the thermal transport properties of explosive hot spots with realistic initial structures throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…This excess PE is the result of large intramolecular deformations that do not significantly relax on timescales comparable to the onset of exothermic chemistry. Nonreactive, hotspot thermal conduction simulations in TATB showed that hotspots formed from the collapse of 40 nm pores take nearly a full nanosecond to equilibrate with the surrounding material . Assessments on the decay of the PE hotspot show almost no relaxation of intramolecular deformations within ∼200 ps of collapse, well within the typical timescale of exothermic relaxation in similar reactive pore collapse simulations. , …”
Section: Introductionsupporting
confidence: 54%
“…This excess PE is the result of large intramolecular deformations that do not significantly relax on timescales comparable to the onset of exothermic chemistry. Nonreactive, hotspot thermal conduction simulations in TATB showed that hotspots formed from the collapse of 40 nm pores take nearly a full nanosecond to equilibrate with the surrounding material . Assessments on the decay of the PE hotspot show almost no relaxation of intramolecular deformations within ∼200 ps of collapse, well within the typical timescale of exothermic relaxation in similar reactive pore collapse simulations. , …”
Section: Introductionsupporting
confidence: 54%
“…35,39 This energy localization, in the form of intra-molecular potential energy, is persistent well into reaction timescales. The increase in strain energy in TATB is caused primarily by torsional and out-of-plane deformations of the nitro and amino groups, shown in Section S5 of the SI, and incurs a local amorphization of the material that affects kinetics 59 and heat transport 60 .…”
Section: Role Of Many-body Strains In the Thermal Decomposition Of Tatbmentioning
confidence: 99%
“…The initiation of chemical reactions and transition to detonation in composite HE formulations under dynamical loading is dominated by energy localization into hotspots via the interaction of the shockwave with the microstructure 19 . These hotspots are almost exclusively characterized by their temperature fields [20][21][22][23] . However, recent molecular dynamics (MD) simulations indicate a deviation from this traditional picture.…”
mentioning
confidence: 99%
“…The initiation of chemical reactions and transition to detonation in composite HE formulations under dynamical loading is dominated by energy localization into hotspots via the interaction of the shock wave with the microstructure . These hotspots are almost exclusively characterized by their temperature fields. However, recent molecular dynamics (MD) simulations indicate a deviation from this traditional picture. Dynamical hotspots can be significantly more reactive than thermodynamically equivalent ones created under nonshock conditions. , Path-dependent reactivity and mechanochemistry have been proposed to explain these observations.…”
mentioning
confidence: 99%